STRUKTUR DRAMATIK LAKON SEMAR MBANGUN GEDHONG KENCANA SAJIAN KI MUJAKA JAKA RAHARJO - Titin Masturoh (Institut Seni Indonesia Surakarta, 2011)
This discussion aims to find answers to Question: what is the background for the preparation of the play Semar Mbangun Gedhong Kencana and how dramatic structure and characteristics pakelirannya. The problem with this approach will be described dramatic structure that includes text and text structure tekstrur. Based on the obtained results that the approach Mujaka Jakaraharja background in preparing the play Semar Mbangun Gedhong Kencana due order and to maintain the quality he has the motivation, either intrinsic or extrinsic. Dramatic structure of the play Semar Mbangun Gedhong Kencana there are two aspects, namely the aspect of text structure and texture aspects. Aspects of text structure includes plot (plot), character, background (setting), theme and message. While aspects of the textures include a description and analysis of each scene shows the benchmark opinion AL Becker.Key words : structure, dramatic, texture, puppet play